A serological survey and characterization of Getah virus in domestic pigs in Thailand, 2017–2018 - Rattanatumhi, Khwankamon; Prasertsincharoen, Noppadol; Naimon, Nattakarn; Kuwata, Ryusei; Shimoda, Hiroshi; Ishijima, Keita; Yonemitsu, Kenzo; Minami, Shohei; Supriyono; Tran, Ngo Thuy Bao; Kuroda, Yudai; Tatemoto, Kango; et al. (Transboundary and emerging diseases, 2022)
Getah virus (GETV) is a mosquito‐borne RNA virus belonging to the family Togaviridae, genus Alphavirus. GETV infection causes diarrhoea and death in piglets, and reproductive failure and abortion in sows. This study conducted a serological survey of GETV infection among domestic pig populations in Thailand. ELISA was used to analyse 1,188 pig serum samples collected from 11 provinces of Thailand during 2017–2018, with 23.1% of the samples being positive for anti‐GETV antibodies. The positive ratio of anti‐GETV antibodies was significantly higher in nursery (67.9%) and older stages (84.5%) of pigs than in finishing stage (14.2%). Furthermore, we successfully isolated GETV from one pig serum, designated as GETV strain GETV/SW/Thailand/2017, and determined the complete genome sequence (11,689 nt). Phylogenetic analysis demonstrated that our isolate was different from the recent GETV group spreading among pig populations in East Asia and formed a cluster with two GETV strains, namely YN12031 (China, 2015) and LEIV16275Mar (Far‐East Russia, 2007). We concluded that two different GETV groups are currently spreading among pig populations in Asian countries.